2015
DOI: 10.1152/ajpcell.00107.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of DRA recycling in intestinal epithelial cells: effect of enteropathogenic E. coli

Abstract: opathogenic Escherichia coli (EPEC) is a food-borne pathogen that causes infantile diarrhea worldwide. EPEC decreases the activity and surface expression of the key intestinal Cl Ϫ /HCO 3 Ϫ exchanger SLC26A3 [downregulated in adenoma (DRA)], contributing to the pathophysiology of early diarrhea. Little is known about the mechanisms governing membrane recycling of DRA. In the current study, Caco-2 cells were used to investigate DRA trafficking under basal conditions and in response to EPEC. Apical Cl Ϫ /HCO 3 Ϫ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Glotfelty et al (2014) [8] recently described a similar observation, reporting the accumulation of internalized occludin within EPEC infected cells and an EspG1/G2-dependent accumulation of other tight junction proteins within the cytosol. Gill et al (2007) [9] described the EspG-dependent movement of the major apical anion exchanger DRA away from the PM to intracellular compartments during EPEC infection and showed that EspG-mediated reduction of DRA at the plasma membrane is due to a decrease in DRA exocytosis [10]. These observations support our hypothesis that EspG influences the protein composition of the host plasma membrane through modulation of recycling endosomes.…”
Section: Introductionsupporting
confidence: 81%
“…Glotfelty et al (2014) [8] recently described a similar observation, reporting the accumulation of internalized occludin within EPEC infected cells and an EspG1/G2-dependent accumulation of other tight junction proteins within the cytosol. Gill et al (2007) [9] described the EspG-dependent movement of the major apical anion exchanger DRA away from the PM to intracellular compartments during EPEC infection and showed that EspG-mediated reduction of DRA at the plasma membrane is due to a decrease in DRA exocytosis [10]. These observations support our hypothesis that EspG influences the protein composition of the host plasma membrane through modulation of recycling endosomes.…”
Section: Introductionsupporting
confidence: 81%
“…EPEC also modulates intestinal epithelial cell electrolyte transport, reducing the expression of sodium hydrogen exchanger 3 (NHE3), the major intestinal transporter for Na + absorption (Gawenis et al , 2002; Hecht et al , 2004; Hodges et al , 2008). Furthermore, EPEC alters the activity and surface expression of the intestinal Cl − /HCO 3 − exchanger, SLC26A3/DRA, resulting in a reduced Cl − uptake and its accumulation in the lumen, driving water loss (Gill et al , 2007; Gujral et al , 2015). EPEC effectors EspF, Map, Tir, and Intimin, act together to inactivate SGLT-1, a cotransporter responsible for 70% of the total fluid uptake by the small intestine (Dean et al , 2006; Meinild et al , 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Map and NleH1 bind to Na + /H + exchanger regulatory factors I and II (NHERF1/2), and Map regulates NHERF1 activity (Simpson et al , 2006; Martinez et al , 2010). EPEC also inhibits the activity of the Cl − /HCO 3 − exchanger, SLC26A3 (Down Regulated in Adenoma, DRA), and this process is mediated by EspG1/G2 effectors (Gill et al , 2007; Gujral et al , 2015). …”
Section: Introductionmentioning
confidence: 99%
“…This price gap has greatly expanded, and 125 I − is now >1/500th the cost of 36 Cl − . More recently, 125 I − has been used to measure Cl − –HCO 3 − exchange activity and Cl − absorption by cultured Caco‐2 cells (Gujral et al., ; Kravtsov et al., ; Kumar et al., ) and everted gut sacs of mouse large intestine (Saksena et al., ), respectively. However, neither reported a direct comparison of I − with Cl − and, although the latter study was the first instance in which 125 I − was used to examine Cl − transport by epithelia, it presented only a single unidirectional flux.…”
Section: Introductionmentioning
confidence: 99%